تأثير جائحة كورونا (كوفيد-19) على مبدأ حرية ممارسة النشاطات التجارية - ضويفى، محمد; بن مبارك، راضية Bin Mubarak, Radiah (جامعة الجزائر1 بن يوسف بن خدة, 2020)
The Corona (Covid-19) pandemic which appeared in 2020 has caused a global crisis in various ways; an economic, financial, social, and health crisis. On the economic side, this pandemic has affected a well-known principle in the commercial law, which is the freedom to carry out commercial activities in which the public authorities issued several regulatory texts where some commercial activities were restricted and suspended. Restrictions were also imposed on movement of individuals due to the seriousness of this virus and the speed of its spread from human to human. in addition to that, health measures have been taken to prevent the spread of this virus, all of this would affect the freedom to exercise commercial activities. In this article, we have tried to search for how to reconcile measures to prevent Corona virus and the principle of commercial activities' freedom.
لقد تسببت جائحة كورونا (كوفيد-19) التي ظهرت سنة 2020 في أزمة عالمية مختلفة الأبعاد، أزمة اقتصادية، أزمة مالية، أزمة اجتماعية، أزمة صحية، أما في الجانب الاقتصادي فقد أثرت هذه الجائحة على مبدأ معروف في القانون التجاري ألا وهو حرية ممارسة النشاطات التجارية، بحيث أصدرت السلطات العمومية عدة نصوص تنظيمية تم فيها تقييد وتعليق ممارسة بعض النشاطات التجارية، كما تم فرض قيود على حركة تنقل الأفراد نتيجة خطورة هذا الفيروس وسرعة انتشاره من الإنسان إلى الإنسان، إلى جانب ذلك تم اتخاذ إجراءات صحية للوقاية من تفشي هذا الفيروس، كل هذا من شأنه التأثير على حرية ممارسة الأنشطة التجارية، وقد حاولنا في هذا المقال البحث عن كيفية التوفيق بين إجراءات الوقاية من فيروس كورونا ومبدأ حرية ممارسة الأنشطة التجارية.
Keywords: فيروس كورونا "كوفيد-19" -- التدابير الوقائية -- الأنشطة التجارية -- القانون التجاري